Principles of managerial finance - Zutter, Chad J.; Smart, Scott B. (Pearson Education Limited, 2022)
For introductory courses in managerial finance. Using financial concepts to solve real-world problems with a proven teaching and learning framework. The Teaching and Learning System - a hallmark feature of Principles of Managerial Finance - weaves pedagogy into concepts and practice, giving students a roadmap to follow through the text and supplementary tools. The 16th Edition concentrates on the material students need to know in order to make effective financial decisions in an increasingly competitive business environment. It allows students to make the connections between a firm's action and its value, as determined in the financial market. With a large number of examples, this text is an easily accessible resource for in- and out-of-class learning.